Efficacy and Safety of Lung Volume Reduction with Endobronchial Coil #2 and Coil #4 Results of the German Emphysema Registry—Lungenemphysemregister e.V. - Christian Grah; Shiao Li Oei; Joanna Krist; Björn Wiesemann; Bernd Schmidt; Andreas Fertl; Björn Schwick; Ralf-Harto Hübner; Birgit Becke; Karl-Josef Franke; Christian Geltner; Stephan Eisenmann; et al. (COPD)
Background Clinical trials have shown beneficial results from lung volume reduction with endobronchial coils in patients with emphysema, but comprehensive safety data are not yet available for a new coil type, Coil #4. The objective of this study is to generate real-world data (RWD) on the safety and efficacy of endobronchial Coil #2 and Coil #4.Methods This is a cohort study of prospectively collected data from the multicenter German Lung Emphysema Registry e.V. (LE-Registry) for patients with advanced lung emphysema undergoing lung volume reduction. All patients treated with Coil #2 or Coil #4 were evaluated at baseline and at 3 months for pulmonary function tests (FEV1, FVC, RV, DLCO, pCO2), exercise capacity, quality of life (mMRC, CAT, SGRQ), and adverse events. Descriptive statistics were used to analyze response rates and changes in clinical outcomes.Results Data from 73 patients (37 Coil #2, 36 Coil #4) enrolled between 2017 and 2024 were evaluated. At 3 months, outcome data were available for 32 Coil #2 and 26 Coil #4 patients. In the Coil #2 cohort significant improvements in RV and SGRQ were observed. The Coil #4 cohort shows significant improvements in FVC, RV, SGRQ, and CAT. Complications occurred in 37% of Coil #2 and 37% of Coil #4 patients, with 26% of patients treated with Coil #4 experiencing pneumothorax.Conclusions The outcomes observed in this RWD study are consistent with other published coil studies. The higher pneumothorax rate with Coil #4 is surprising and should be minimized by adapting the technique.Trial registration DRKS00021207 registered on 29/05/2020.